Importance of MCDM in Labor Productivity for Construction Projects (Latakia University Journal -Engineering Sciences Series, 2020)
This study presents " Importance of MCDM in labor productivity for construction projects", and the purpose of the research is to highlight the importance of adopting the multi-criteria decision-making methodology MCDM in the productivity of construction projects, which relates to many influencing factors such as planning and control, the approved construction method or the use of modern technology, in addition to conditions Safety and security in the workshop, environmental factors, and other factors affecting on work productivity in various degrees, Where it is considered that the best decision-making methodology between a group of available alternatives is a flexible solution and a suitable tool for the decision-maker, for the contractor or the engineer through comparison between the set of main and sub-factors affecting on work productivity and knowing the magnitude of the impact of each of them, to reach a right decision in Productivity evaluation, and to give a clear picture for finding possible engineering solutions, which contribute to raising the efficiency of work and its effectiveness when implementing the construction project . تتناول هذه الدراسة " أهمية MCDM في إنتاجية العمل للمشاريع الإنشائية "، والغرض من البحث هو إبراز أهمية اعتماد منهجية اتخاذ القرار المتعدد المعايير MCDM في إنتاجية العمل للمشاريع الإنشائية، والتي تتعلق بالعديد من العوامل المؤثرة كالتخطيط والمراقبة، وأسلوب البناء المعتمد أو استخدام التكنولوجيا الحديثة، بالإضافة الى شروط الامن و السلامة ضمن ورشة العمل، والعوامل البيئية، وغيرها من العوامل التي تؤثر على إنتاجية العمل بدرجات مختلفة، حيث تعتبر منهجية اتخاذ القرار الأفضل بين مجموعة البدائل المتوفرة حل مرن وأداة مناسبة لصاحب القرار سواء أكان المقاول أو المهندس المشرف، من خلال المقايسة بين مجموعة العوامل الرئيسية و الفرعية المؤثرة على إنتاجية العمل و معرفة حجم تأثير كل منها ، للوصول إلى قرار سليم في تقييم الإنتاجية، وإعطاء صورة واضحة لإيجاد الحلول الهندسية الممكنة ، التي تساهم في رفع كفاءة العمل و فعاليته عند تنفيذ المشروع الإنشائي.